Pelatihan Internalisasi Penguatan Peran Perempuan (Istri Pejabat) dalam Pembangunan Budaya Integritas - Aully Grashinta; Farida Aini; Ni Made Rai Kistyanti; Fasya Azzahra P.H. (Devotion : Jurnal Pengabdian Psikologi, 2023)
Corruption is a phenomenon that still occurs in Indonesia. This condition encourages concrete steps to be taken so that acts of corruption can be prevented, one of which is by involving the role of officials' wives in the government environment. It is considered important for wives to be involved in preventing and eradicating corruption because basically, wives have a big influence on the decisions taken by their husbands, who in this case are in office. Therefore it was held "Training of Internalization Strengthening The Role of Women (Wives of Government Officials) on Developing a Culture of Integrity". The training aims to internalize the nine core values of integrity, which are Jujur (honesty), Mandiri (independence), Tanggung jawab (responsibility), Berani (courage), Sederhana (simplicity), Peduli (care), Disiplin (discipline), Adil (fairness), and Kerja Keras (hard work), it’s called “Jumat Bersepeda KK”. The Integrity Training was delivered using experiential learning methods that were known to enhance the learning process through concrete experiences designed for individual or group activities. Through the execution of this training, it can be concluded that the aim of the training was achieved, as evidenced by the participants' ability to draw insights and their enthusiasm in asking questions during the training sessions. Further development of this program is by implementing pre-test and post-test measurements to assess the effectiveness of the training.